HOSPITAL-BASED HEALTH TECHNOLOGY ASSESSMENT (HB-HTA): A 10-YEAR SURVEY AT ONE UNIT. (5th August 2016) - Grenon, Xavier; Pinget, Christophe; Wasserfallen, Jean-Blaise
Abstract : Introduction: Hospital-based health technology assessment (HB-HTA) has been introduced to help hospital management in decision making about the adoption of new health technologies (HTs). We reviewed the accuracy of the expected medical impact of HTs assessed at our hospital, as well as the acceptance of this process by clinicians. Methods: For each HT adopted between 2002 and 2011, a semi-structured interview with the involved clinician was conducted, assessing (i) the perceived utility of the HB-HTA process, (ii) the accuracy of the new HT's expected medical impact as compared with observed patient data from the year 2012, and (iii) the compliance with the indications of the HB-HTA report. Results: Over the 10-year period, forty HB-HTAs were carried out, of which thirty-four led to acceptance. Twenty-seven of the twenty-eight clinicians involved in these thirty-four HTs accepted the interview and 85 percent acknowledged the utility of the HB-HTA process. Five of the thirty-four HTs were no longer in use. For the twenty-nine remaining HTs, observed patients' number was as expected in eight, higher in four, lower in fifteen, and not available in two cases. Available average length of stay was 61 percent longer than expected. Two HTs had a higher complication rate and three a lower success rate. Indications evolved in 55 percent of HTs after a few years (seven restrictions, six broadenings, and three other changes). Conclusions: A HB-HTA process is useful to improve quality in decision making. Follow-up analysis should routinely be performed to adapt HB-HTA reports' conclusions to practical experience and new scientific evidence.